La gobernanza global de la salud y los límites de las redes de expertos en la respuesta al brote de la Covid-19 en México - Coronado Martínez, María Esther (El Colegio de México A.C., 2021)
This study argues that the global health governance system has led to the formation of a number of expert networks that serve as mechanisms for the circulation of evidence-based ideas and that promote cooperation and the implementation of World Health Organization (who) recommendations. However, the outbreak of Covid-19 has brought to light the limitations of these networks. In the case of Mexico, two principal problems have been observed: first, the existence of experts who belong to a cross-governmental network and who make decisions based on political interest, to the detriment of global recommendations; and second, a divided knowledge community of rival groups that damages the actions of these experts in their efforts to transmit ideas and spread knowledge.